Perencanaan, Pengorganisasian, Menggerakan, dan Mengontrol Sumber Daya Manusia - Zulkifly A. Lasena; Noviyanti Djafri Arifin Suking (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
uman Resource Management (HRM) involves determining planning, organizing, implementing, and monitoring to achieve organizational goals with a primary focus on human resources, namely employee management, employee potential development, service provision, employee behavior direction, and employee discipline supervision. This ensures that human resources can demonstrate the optimal performance demanded by the company to achieve the goals set by the organization. This article falls under the category of qualitative research with a literature review approach (library research). The collection of journals related to the theme aims to gather data and information related to genetic, social, and ecological leadership theories. The sources used include books or articles obtained from physical forms and other applications such as Google Scholar, Mendeley, ScienceDirect, and others. Human Resource Management (HRM) is a discipline responsible for managing people in an organization. This includes planning, organizing, directing, and controlling human resources to achieve organizational goals effectively and efficiently. HRM plays a role in managing various aspects related to employees, such as recruitment, selection, training, development, motivation, performance evaluation, and compensation. Human resource control must be holistic, employee-oriented, and integrated with the organization's business strategy. Therefore, it can be concluded that this involves the use of various tools and techniques, including performance measurement, structured feedback, employee development, and the implementation of fair and consistent policies and procedures.